2013
DOI: 10.4062/biomolther.2013.001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Quercetagetin, an Active Component of Immature Citrus unshiu, in HaCaT Human Keratinocytes

Abstract: Citrus fruit contain various flavonoids that have multiple biological activities. However, the content of these flavonoids are changed during maturation and immature Citrus is known to contain larger amounts than mature. Chemokines are significant mediators for cell migration, while thymus and activation-regulated chemokine (TARC/CCL17) and macrophage-derived chemokine (MDC/CCL22) are well known as the typical inflammatory chemokines in atopic dermatitis (AD), a pruritic and chronic inflammatory skin disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Quercetagetin (3, 5, 6, 7, 3', 4'-hexahydroxyflavone) [6], a characteristic flavonol compound with six additional phenolic hydroxyl groups based on the molecular structure of the flavones backbone, is widely distributed in the Calendula officinalis which was famous for its anti-inflammatory and anti-cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetagetin (3, 5, 6, 7, 3', 4'-hexahydroxyflavone) [6], a characteristic flavonol compound with six additional phenolic hydroxyl groups based on the molecular structure of the flavones backbone, is widely distributed in the Calendula officinalis which was famous for its anti-inflammatory and anti-cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…1). There are many reports focused on its antioxidant activity (Gong et al 2012a, b;Xu et al 2014), antiinflammatory activity (Kang et al 2013) and copigment effect (Xu et al 2015). Some scientific researches reported that quercetin has strong inhibition of α-glucosidase, α-amylase and lipase (Dong et al 2012;You et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Snakegourd root, a main component of snakegourd fruit, has immunoregulatory function that helps resist hypoxia, activates immunocytes, and increases the ability to defend against infections Xu et al, 2010;Yan et al, 2012). Immature orange fruit relieves constipation, displays anti-inflammatory and antioxidant effects (Menichini et al, 2011;Kang et al, 2013;Yu et al, 2013), promotes gut hormone secretion, and improves gastrointestinal motility (Wu et al, 2011;Lyu and Lee, 2013). Rhubarb and goldthread clear away heat-evil and expel superficial evils, and thus have a positive therapeutic impact on pancreatitis (Wu et al, 2000;Wang et al, 2007;Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%